Co-extraction of tungsten and molybdenum from refractory scheelite–powellite blend concentrates by roasting with Na2CO3 and SiO2 and leaching with water. (2nd October 2018) - Yang, Weizheng; Wang, Wu; Wu, Xiaochao; Yang, Kaijun; Li, Qingkui; He, Jilin
ABSTRACT: Studies on the recovery of tungsten and molybdenum from refractory scheelite–powellite blend concentrates – mainly composed of scheelite, powellite, and fluorite – were performed using soda-silicon roasting and water leaching processes. However, significant amounts of scheelite and powellite ore are present in an intergrowth state and the application of mineral dressing is not suitable for the separation and extraction of tungsten and molybdenum from this refractory ore. The effects of roasting parameters including sodium carbonate addition, roasting temperature, roasting time, and mass ratio of SiO2 /concentrate ( w SiO2 / w conc. ) and the effects of leaching parameters including leaching temperature, leaching time, and liquid-to-solid ratio on the leaching efficiency of tungsten and molybdenum were investigated. The results demonstrated the efficiency of this process for the extraction of tungsten and molybdenum from the ore. Under the optimum experimental conditions where soda-silicon roasting is performed for 2 h at 850°C with three times, the stoichiometric ratio of Na2 CO3 (Na2 CO3 :WO3 and Na2 CO3 :MoO3 ) and w SiO2 / w conc of 12%, and water leaching is subsequently performed for 1 h at 70°C with a liquid-to-solid ratio of 3:1, the leaching ratios of W and Mo are 98.89% and 99.41%, respectively.